Amamentar e doar leite: percepções das mulheres doadoras de um Banco de Leite Humano - Mateus Guilhardi Rosa e Silva; Karen Cristine Almeida Barbosa; Lorrayne Aparecida Silveira Borges; Guilherme Ferreira Barros; Lucas Gundim Cardoso; Marluce Martins Machado da Silveira (UniEVANGÉLICA, 2018)
Objective: To describe and analyze the factors that facilitate the donation of breast milk as well as the difficulties in the perspective of the women donor. Itis a qualitative research, descriptive-exploratory, and the method of hermeneutic-dialectical analysis objectified by Minayo, in which the members are women donors of the Human Milk Bank in the period of one month. The women's speech analysis has allowed to verify the main motivator for the breastfeeding practice is the knowledge of the benefits of breastfeeding, while for the milk donation practice were the "excess of milk", the correlation with mothers whose infants need the donated breast milk and to help others. The difficulties in breastfeeding were analyzed, described as the wrong-handle and the perception of "weak milk and few milk". The importance of family and the health team support were verified, besides the knowledge of Human Milk Bank. It is perceived that many mothers are aware of the importance of breastfeeding; however, the women donors experience the same difficulties reported in studies on reasons for weaning, and the support and guidance received in the Human Milk Bank were fundamental forbreastfeeding and for the donation of breast milk.